MODERN TECHNOLOGY OF TREATMENT OF PATIENTS WITH CICATRICAL DEFORMITIES OF THE FOOT AND ANKLE JOINT (Academicia Globe: Inderscience Research, 2022)
This article gives detailed information on how deformities of the foot and ankle joint are treated nowadays. In this article analysis on the factors rendering this case common are mentioned and pertinent solutions to avoid it have been provided.